Pendidikan Komunikasi dalam terang Misi sebagai Dialog Profetis - Soge, Aurelius Pati (Perspektif, 2007)
Living in a plural society like today, the Church is challenged to update its mission in order to meet the need of the society. The plurality has served as a new context of the mission which the Church is obliged to bring about. While the idea of spreading the Good News remains intact, the methods need to be updated. It has to change along with the social development. There are various responses the Church has initiated for years, however, the actual need is very much shaped by the model of dialog. The dialog requires the change of mentality, as every person engaged in this process is considered partner, which means "we are on the same level", together moving along to find the truth, the Divine Salvation. No doubt, the mission as a process of prophetic dialog comes into the light of the new progress of modern missiology. Based on this new paradigm of the mission, every missionary is expected to develop its basic communication skill and attitude. This article discuss this focal point, how to develop such basic attitude and skill in order to execute the mission givent o the Church by Jesus Christ in a modern and plural world, which is very much characterized by the modern communication. Missionaries should have their basic communication skill. Meanwhile, they also need to Hat develop the sort of communication personality, which will help them to communicate the presence of God and His plan to save all human kind. The author proposes that the period of formation is a perfect time to develop that particular requirement. However, they also need to update themselves during the time of services in the program of on-going formation.